Eco-Friendly Management of Diamondback Moth (Plutella xylostella L.) of Cabbage (Brassica oleracea var. capitata) in Nepal - Parajuli, Sovit; Paudel, Sandip (International Journal of Applied Sciences and Biotechnology, 2019)
Cabbage is a popular cruciferous vegetable crop consumed for various purposes not only in the world, but also in Nepal. Among several pests, Diamondback moth (Plutella xylostella.L.) is a primary pest causing heavy loss of cabbage field each year in Nepal. Damage is caused by larvae. The trend of extensive and unscientific use of insecticide has resulted a devastating loss in cabbage production (31%-100%) and economic yield (US 4-US5billion each year) on one hand and challenging the environment on the other hand. Thus integrated pest management practices, including botanical, biological, cultural methods and use of resistant varieties are effective. Annosom (extract of Annona spp.1%) and Neemix (extract of Azadirachta indica, 60%w/w) are effective botanical pesticides. Diadegma spp, among various biological control agents, is effective. Two rows of mustard for every twenty-five rows of cabbage is effective trap cropping. Yellow sticky trap is best for DBM monitoring and control. The seasonal irrigation and rain interferes the mating and oviposition and thus control of the pest. Spinosad, Indoxacarb and Emamectin benzoate are mostly used insecticides for the control of this moth. Use of specific resistant varieties like, G 9101 and G 9619 and transgenic lines are effective but in Nepalese context, least adopted by Nepalese farmers. Int. J. Appl. Sci. Biotechnol. Vol 7(3): 304-308